mRNA splicing in turkey muscle satellite cells is dynamically altered upon thermal challenge - Ashley A. Powell; Gale M. Strasburg; Sandra G. Velleman; Kent M. Reed (PLoS ONE, 2026)
Regulation of gene expression at the transcriptional and post-transcriptional levels is essential for proper development and growth, with tightly coordinated cellular processes supporting key biological functions. While transcription determines the available mRNA pool, post-transcriptional modifications such as alternative splicing (AS) increase transcriptome complexity and enable the production of diverse protein isoforms. In muscle, AS is critical in generating muscle-specific proteins required for normal development and function and may be particularly susceptible to disruption by thermal stress. This study examines how thermal challenges—both cold and heat—affect muscle biology by analyzing AS events during the proliferation and differentiation of skeletal muscle satellite cells (SCs). Isoform identification and AS analyses were performed on RNA-seq data from a prior study of skeletal muscle SCs derived from commercial turkeys and exposed to three temperature conditions (33°C, 38°C, or 43°C) during proliferation or differentiation. Analyses revealed 61,266 predicted splicing events across 5,202 annotated genes. Significant differential splicing was observed in all temperature comparisons, and between proliferating and differentiating cells at each temperature. Additionally, there was a strong association between differentially spliced genes (DASs) and differentially expressed genes (DEGs). This study provides a comprehensive catalog of splice isoforms for future functional analyses, many of which are likely to result in protein variants that influence SC proliferation, differentiation, and ultimately, muscle development and performance.